2014
DOI: 10.1155/2014/468925
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Posttranslational Modifications in Peroxisome Proliferator-Activated ReceptorγUsing Mass Spectrometry

Abstract: Posttranslational modification (PTM) of proteins is critical for various cellular processes. However, there are few studies examining PTMs in specific proteins using unbiased approaches. Here we report the attempt to identify the PTMs in peroxisome proliferator-activated receptor γ (PPARγ) proteins using our previously established PTM analysis system. In this study, we identified several PTMs in exogenously expressed PPARγ2 proteins from 293T cells as well as endogenous PPARγ1 proteins from a Caco-2 colon canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Then, coactivators, such as steroid receptor coactivators, PPARγ coactivator 1s, histone acyltransferases, and the mediator complexes, are recruited and interact with PPARγ to promote gene transcription 10 , 14 , 15 . In addition to ligands, post-translational modifications (PTMs), including phosphorylation, SUMOylation, acetylation, and ubiquitination, are considered as some of the major processes regulating the transcriptional activity of PPARγ 16 , 17 . Phosphorylation of PPARγ at Ser112 by mitogen-activated protein kinase suppresses PPARγ transcriptional activity and adipocyte differentiation 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Then, coactivators, such as steroid receptor coactivators, PPARγ coactivator 1s, histone acyltransferases, and the mediator complexes, are recruited and interact with PPARγ to promote gene transcription 10 , 14 , 15 . In addition to ligands, post-translational modifications (PTMs), including phosphorylation, SUMOylation, acetylation, and ubiquitination, are considered as some of the major processes regulating the transcriptional activity of PPARγ 16 , 17 . Phosphorylation of PPARγ at Ser112 by mitogen-activated protein kinase suppresses PPARγ transcriptional activity and adipocyte differentiation 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The chemical ligands have been developed into therapeutic drugs for the treatment of type 2 diabetes. In addition to the ligand activation, PPARγ can also be regulated through diverse posttranslational modifications [16]. In recent years, it has been found that PPARγ serine 245 (or S273 in PPARγ isoform 2) can be phosphorylated by cyclin-dependent kinase 5 (CDK5), and this posttranslational modification is related with insulin resistance in obese individuals [17].…”
Section: Introductionmentioning
confidence: 99%
“…This finding provides a link between the regulation of AMPK and PPARγ. In the literature, CDK5 is reported to regulate posttranslational modifications of PPARγ [16]. Phosphorylation of PPARγ at serine 273 by CDK5 has been shown to stimulate diabetogenic gene expression in adipose tissues [17].…”
mentioning
confidence: 99%
“…Given the importance of PPARγ in various physiological and pathological processes, PPARγ gene regulation has been extensively studied at the genomic and transcriptional levels in recent decades (Lee and Ge, 2014). The half-life of PPARγ mRNA and protein is short and PPARγ protein can be post-translationally modified in various ways (van Beekum et al, 2009;Katsura et al, 2014), suggesting that posttranscriptional regulation is crucial for its function. However, to date, posttranscriptional regulation by the 5 UTR has been mostly unexplored.…”
Section: Introductionmentioning
confidence: 99%